Perancangan Industri Kaorseri Bis Dengan Tema Ekspresi Struktur Di Wilayah Tangerang Selatan - Abdul Najib Farkhan; Sri Kurniasih (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
Bus Body Car is an industry that is engaged in the manufacture of medium bus and large bus bodies. Starting from the making of a bus manufacturing framework, bus body fitting, painting, and ending with finishing the interior and exterior with national standards all designed in the Design of the Bus Body Industry. The purpose is to build a car body in South Tangerang to facilitate access for the approved owner directly and see how the bus was made, to discuss and sell a product, it requires a design concept that attracts attention in addition to the product design of the building also needs to be displayed using Express Structure caught the attention of road users and as bus owners.